The Boneshaker - Milford, Kate (Clarion Books, 2010)
When Jake Limberleg brings his traveling medicine show to a small Missouri town in 1913, thirteen-year-old Natalie senses that something is wrong and, after investigating, learns that her love of automata and other machines make her the only one who can set things right.